PENGELOLAAN LEMBAGA PENDIDIKAN BERBASIS SNP DALAM RANGKA PENCAPAIAN TUJUAN PENDIDIKAN (SEBUAH STRATEGI PENERAPAN FUNGSI MANAJEMEN DALAM PENGEMBANGAN STANDAR NASIONAL PENDIDIKAN DI PTAI) - ARDIMEN ARDIMEN (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
Standar Nasional Pendididikan (SNP) has set minimum criteria of Educational system in Indonesia. It has functions as the foundation for planning, actualizing and controlling in education in Indonesia, including for Islamic higher education, in the efforts of achieving qualified education. Islamic higher educational institutions (PTAI) need to formulate and develop SNP in accordance with the characteristics of vision, mission, standard competemcy of the graduates, particular features of the majors developed in PTAI. SNP-based educational institution management is an important element to arrive at educational goals. Consequently, managerial activities applying functions of management systemically and systematically is very essential in the development of SNP.Kata kunci: pengelolaan, lembaga pendidikan, SNP